The role of groupwork in tackling organisational burnout - Carson, Jerome; Dennison, Paul (Groupwork, 2012)
The issue of occupational burnout is a concern to managers as it impacts on the quality of client care. Burnout is said to comprise three elements. These are a high level of emotional exhaustion, a low sense of personal accomplishment and the development of an unfeeling, so-called depersonalised approach towards service users. In this paper, we describe two contrasting approaches that used groupwork to tackle the problem of staff stress and burnout in mental health workers. The first used three-day self-esteem workshops. The second used staff support groups that were run fortnightly over a five-year period. Both approaches have their merits. While the concept of burnout is essentially a negative one, there may be a role for developing alternative approaches based on positive psychology and attachment theory.